Speed strategy of public administration services in fulfilling the basic rights of citizens in rural areas in Indonesia - Sry Rosita; Andang Fazri; Ratih Kusumastuti; Syahmardi Yacob (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
The main purpose of this research is to examine the speed strategy of public administration services in fulfilling the basic rights of citizens in rural areas in Indonesia. The method in this research is descriptive type with quantitative approach and use explanatory survey. The target of the research was villagers in four districts in Jambi Province. The instrument used to collect the data is by using a structured questionnaire given to the sample respondents. The statistical tool to examine the hypotehsis is by using Partial Least Square (PLS) method with smart-PLS as the software. The study found that the speed strategy of public administration services has a positive and significant influence on fulfilling the basic rights of citizens in rural areas. However, these positive and significant effect towards fulfilling the basic rights of citizens are mediated by public administration services. These suggest that the role of public administration services in rural areas should be transparent, accountable, and it needs to accommodate public participants and public right equally.